Holly's story - McDaniel, Lurlene (New York : Laurel-Leaf Books, 2007)
With the support of her two best friends, high school senior Holly tries to deal with the murder of her brother and her anger at God for allowing the crime to happen.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Brothers and sisters -- Juvenile fiction; Christian life -- Juvenile fiction; Friendship -- Juvenile fiction; Grief -- Juvenile fiction; Murder -- Juvenile fiction; Brothers and sisters -- Fiction; Christian life -- Fiction; Friendship -- Fiction; Grief -- Fiction; Murder -- Fiction; Christian fiction; Christian life -- Fiction; Friendship -- Fiction; Grief -- Fiction; Homicide -- Fiction; Siblings -- Fiction; Florida -- Fiction; Florida -- Fiction; Christian fiction